Stable extracellular RNA fragments of Mycobacterium tuberculosis induce early apoptosis in human monocytes via a caspase-8 dependent mechanism (2012)
ABSTRACT: The molecular basis of pathogen-induced host cell apoptosis is well characterized for a number of microorganisms. Mycobacterium tuberculosis is known to induce apoptosis and it was shown that live but not heat killed M. tuberculosis stimulates this biological pathway in monocytes. The dependence of this activity on live bacilli led us to hypothesize that products released or secreted by M. tuberculosis are the primary apoptotic factors for human monocytes. Thus, the culture filtrate of in vitro grown M. tuberculosis strain H37Rv was fractioned by conventional chromatography and the apoptosis-inducing activity of individual fractions was measured on human monocytes. The tests employed included measurement of cell membrane damage, caspase activation, and cytokine release. Small molecular weight RNAs of M. tuberculosis were recognized as the predominant apoptosis inducing factors. The RNA was comprised primarily of tRNA and rRNA fragments that stably accumulate in the culture filtrate during early log-phase growth. The RNA fragments signaled through a caspase-8 dependent, caspase-1 and TNF-α independent pathway that ultimately compromised the human monocytes' ability to control M. tuberculosis infection. These studies provide the first report of bacterial RNA inducing apoptosis. They also provide a foundation to pursue pathways for secretion or release of nucleic acids from M. tuberculosis and the impact of secreted RNA fragments on pathogenesis.